Health Education on Mother's Knowledge and Skills in Care of Kanguru Methods in LBW In Peristi's Room at Mokopido Tolitoli Hospital - Ilmiati, Ilmiati (Chakra Brahmanda Lentera Institute, 2021)
Background: In Indonesia, it is estimated that one baby dies every six minutes, one of which is due to having a low body weight. One way to prevent babies from dying from low weight is to use the kangaroo method. Objective To find out the effect of Health Education on the Knowledge and Skills of Mothers in Kangaroo Method Care at LBW in the Hospital Room at Mokopido Tolitoli Hospital. Methods: The design used in the study was pre-experiment, one group pre-posttest. Population is All Mothers of a Baby. The sample size is 30 respondents using accidental sampling technique. Independent variables of the study were counseling about the kangaroo method on LBW. The dependent variable is knowledge and skills. Data was collected using a questionnaire, then data were analyzed using the Wilcoxon test with a significance level of α ≤ 0.05. Results: The results showed that respondents had less knowledge before health education as many as 24 respondents (80%), good knowledge after health education as many as 22 respondents (73.3). unskilled, need help before health education as many as 26 respondents (86.7%), independent after health education after health education, as many as 26 respondents (86.7). The results obtained by statistical test results found that the knowledge of respondents before and after health education p <a with a = 0.05, which means that there is a significant effect of health education on knowledge (p = 0,000), and skills (p = 0,000) Conclusion: The discussion of this study was an assessment of the knowledge and skills of women in PMK in LBW infants before dna after being educated about the use of a good and effective method of kangaroos to help the baby maintain the stability of the baby's temperature.